Liderança pedagógica na educação infantil: percepções relatadas por diretoras da rede municipal de Patos-PB sobre sua atuação - Silva, Camila Martins de Souza (Universidade Federal de São Carlos, 2025)
This dissertation investigates the role of early childhood education principals in the municipality of Patos-PB, through the lens of instructional leadership and in alignment with the official documents that guide this educational stage. The research addresses a gap identified in the literature regarding the leadership exercised by school principals in Early Childhood Education, especially in municipal contexts in the interior and Northeast regions of Brazil. The general objective was to characterize principals’ perceptions of their roles, practices, and challenges, as well as the institutional support they receive, based on semi-structured interviews conducted with ten school leaders. The qualitative analysis of the data followed the Content Analysis technique (BARDIN, 2016) and was organized into four parts: (i) characteristics of instructional leadership; (ii) self-assessment and motivations regarding their roles; (iii) support from the Municipal Department of Education; and (iv) challenges faced. The results reveal that, although there are convergences with the pedagogical management dimension and the social function of Early Childhood Education, there is a lack of tools and guidelines for the exercise of instructional leadership, as well as a gap in the establishment of specific goals for this stage. In the context of Patos, relational leadership stands out, based on care and active listening. The research connects international frameworks on instructional leadership (LEITHWOOD, 2004; ROBINSON, 2008; FABRY, 2022) with national regulatory frameworks (BNCC, DCNEI, PNQEI), contributing to the debate on improving educational management in Early Childhood Education. The findings provide insights for training policies that recognize the specificities of this stage and strengthen the role of principals as instructional leaders.
Instructional leadership in early childhood education: principals’ self-reported perceptions in Patos, Paraíba (Brazil)
Keywords: Educação infantil; Liderança pedagógica; Diretor escolar; Gestão educacional; Qualidade da educação infantil; Early childhood education; Instructional leadership; School principal; Educational management; Quality of early childhood education; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL; 4. Educação de Qualidade